THE CONTRIBUTION OF NICE FRACILE TO THE STUDY OF THE MUSICAL FOLKLORE OF VOJVODINA - IVKOV, Vesna (Studia Universitatis Babes-Bolyai Musica, 2023)
The immediate motive to produce this study is the marking of significant anniversaries in the field of ethnomusicology, both in the personal life of famous ethnomusicologist Nice Fracile and in the activities of the Academy of Arts of the University of Novi Sad. By reviewing the moments from the life and professional experience of this ethnomusicologist, an insight and a guide is offered into the possibilities of creativity and advancement of an individual, who has made a significant scientific contribution to local, regional and world ethnomusicology by studying the musical tradition of his community, and later the wider area as well.